The New Testament and early Christian literature in Greco-Roman context : studies in honor of David E. Aune - Aune, David Edward.; Fotopoulos, John, 1967- (Novum Testamentum, Supplements, 2006)
This volume is a collection of scholarly studies honoring Prof.Dr. David. E. Aune on his 65th birthday. Its title, The New Testament and Early Christian Literature in Greco-Roman Context: Studies in Honor of David E. Aune , reflects Prof. Aune's academic training, interests, and extensive publications. The volume's studies investigate a range of topics within the Pauline correspondence, Gospels, Apocalypse of John, and other early Christian writings with insights drawn from Greco-Roman culture and Hellenistic Judaism. Thus, the studies make use of Greco-Roman literature, rhetoric, magic, medicine, moral philosophy, iconography, archaeology, religious cults, and social conventions while also utilizing social-historical, social-scientific, literary-critical, and rhetorical-critical methodologies, thereby adding an interdisciplinary dimension to the volume. These groundbreaking studies have been written by prominent international scholars and are published here for the first time.